Reflection and readiness: Shared benefits of using an Oral Final Evaluation to assess counselor competency - Tanya Surette; Kelly Brenton (Teaching and Supervision in Counseling, 2021)
The COVID-19 pandemic has impacted educational systems worldwide, shifting everything from pedagogy to learning environments. The emerging needs and complexities presented during this time has challenged long-standing practices, requiring creativity and innovation to adapt in the midst of uncertainty and accelerated change. This has been the reality within graduate counselling programs where coursework and internships were interrupted, and the counselling environment altered. In the face of such changes, the critical assessment and evaluation of pre-service counsellor competence remains a high priority of counsellor educators. This article outlines the practice of adopting an Oral Final Evaluation (OFE) of post-practicum graduate counselling students as a means of addressing the need to accurately assess counsellor competence in the changed landscape of the current pandemic. This article provides a rationale for integrating an OFE and space for reflection on its implementation, along with feedback from participating students, faculty, and site-supervisors.
Keywords: Counselor competence; COVID-19; professional standards; Oral Final Evaluation; counselor education